LA INNOVACION TECNOLOGICA EN ASERRADEROS DE LA PROVINCIA DE MISIONES, REPUBLICA ARGENTINA - Kerkhoff, Alejandro J.; Dekun, Maria C.; Senn, Jorge; Mantulak, Mario J. (Salão do Conhecimento, 2013)
Resumo